International intervention in Afghanistan : motives and approaches - Basu Roy, Arpita; Misra, Binoda Kumar; Misra, Aliva; Maulana Abul Kalam Azad Institute of Asian Studies (Kolkata, India); Indian Council of World Affairs; International seminar on Rethinking international intervention in Afghanistan (2011) (Delhi : Shipra Pubs., 2012)
Papers presented at an international seminar on Rethinking international intervention in Afghanistan, organised by Maulana Abul Kalam Azad Institute of Asian Studies in collaboration with Indian Council of World Affairs in 2011
Includes bibliographical references and index
Keywords: Diplomatic relations; Afghanistan -- Politics and government -- Congresses; Afghanistan -- Foreign relations -- Congresses